2009
DOI: 10.1016/j.ydbio.2008.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Testis cord differentiation after the sex determination stage is independent of Sox9 but fails in the combined absence of Sox9 and Sox8

Abstract: Sox9 and Sox8 are transcription factors expressed in embryonic and postnatal Sertoli cells of the mouse testis. Sox9 inactivation prior to the sex determination stage leads to complete XY sex reversal. In contrast, there is normal embryonic testis development in Sox8 mutants which are initially fertile, but later develop progressive seminiferous tubule failure and infertility. To determine whether Sox9 is required for testis development after the initial steps of sex determination, we crossed Sox9(flox) mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
153
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 157 publications
(166 citation statements)
references
References 62 publications
10
153
1
2
Order By: Relevance
“…The mutant also indicated that sox9b expression is more intense in the supporting cells surrounding the germline stem cell population than in those that surround the gametogenesis‐committed germ cells 24. The function of germ cell maintenance has also been reported in the mouse adult testis 52. It is speculated that the loss of sox9b function in the germ cell maintenance, in addition to the loss of germline stem cells, allows for the neofunctionalization of the mammalian Sox9 as an effector of Sry .…”
Section: Neofunctionalization Of Other Genes With Loss Of Germline Stmentioning
confidence: 96%
“…The mutant also indicated that sox9b expression is more intense in the supporting cells surrounding the germline stem cell population than in those that surround the gametogenesis‐committed germ cells 24. The function of germ cell maintenance has also been reported in the mouse adult testis 52. It is speculated that the loss of sox9b function in the germ cell maintenance, in addition to the loss of germline stem cells, allows for the neofunctionalization of the mammalian Sox9 as an effector of Sry .…”
Section: Neofunctionalization Of Other Genes With Loss Of Germline Stmentioning
confidence: 96%
“…A deficiency in SOX9 expression in adult life may lead to various abnormalities, from gonadal dysgenesis to transdifferentiation into an ovary (Barrionuevo et al 2009;Barrionuevo et al 2012;Plotton et al 2012). Experiments on SOX9 conditional null mutant mice (Barrionuevo et al 2009) confirmed that SOX9 plays a crucial role in embryonic sex determination. Also, SOX9 together with SOX8 (SRY-box 8 gene) is essential for spermatic cord formation during early testis development.…”
mentioning
confidence: 99%
“…However, the effects of these gene products on postnatal gonadal maturation, how their expression is regulated at different developmental stages, as well as their relationships with other factors are poorly understood. It is known that SOX9 plays a key role in the maintenance of testicular status in mice (Barrionuevo et al 2009;Barrionuevo et al 2012). A deficiency in SOX9 expression in adult life may lead to various abnormalities, from gonadal dysgenesis to transdifferentiation into an ovary (Barrionuevo et al 2009;Barrionuevo et al 2012;Plotton et al 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations